1992
DOI: 10.1136/jnnp.55.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Vertigo and upside down vision due to an infarct in the territory of the medial branch of the posterior inferior cerebellar artery caused by dissection of a vertebral artery.

Abstract: A 48 year old woman developed an acute vestibular syndrome associated with upside down vision a few hours after minor cervical trauma. Magnetic resonance imaging showed an ischaemic lesion in the territory of the medial branch of the posterior inferior cerebellar artery. An arteriogram showed a dissection of the left extracranial vertebral artery.Since the advent of CT small cerebellar strokes are known to present as isolated vestibular, syndromes."5 The pathophysiology of these labyrinthine-like syndromes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…In most cases, inversion or tilt occurs in the frontal plane, but both have also been described in the horizontal and sagittal planes [108,113]. Room tilt illusion has been associated with lesion of the brainstem and vestibulocerebellar system [34,41,71,103,109,111,113], lesions of the parieto-occipital and frontal cortex (see review in [108]), peripheral vestibular disorders [89], and it has even been described in healthy subjects [89,101].…”
Section: Room Tilt Illusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, inversion or tilt occurs in the frontal plane, but both have also been described in the horizontal and sagittal planes [108,113]. Room tilt illusion has been associated with lesion of the brainstem and vestibulocerebellar system [34,41,71,103,109,111,113], lesions of the parieto-occipital and frontal cortex (see review in [108]), peripheral vestibular disorders [89], and it has even been described in healthy subjects [89,101].…”
Section: Room Tilt Illusionmentioning
confidence: 99%
“…See text for explanations (drawings by Lovisa Halje after Blanke et al [14]). respect to their body (and self), called room tilt illusion [34,108,113]. Third, we review conditions of vestibular and multisensory conflicts that are prone to induce body illusions in healthy subjects including astronauts.…”
Section: Introductionmentioning
confidence: 99%
“…Solms et al [2] reported the role of bifrontal abscesses in the occurrence of UDRV. Indeed, the causative factors for this phenomenon include ischemic attacks of the posterior circulation, vertebrobasilar insufficiency, vertebral artery dissection, brainstem, cerebral, and cerebellar lesions, Wallenberg syndrome, head traumas, third ventriculostomy operation for hydrocephaly, and measles encephalitis [1][2][3][4][5][6][7][8][9][10][11]. It is not a usual finding in patients with MS. Dogulu and Kansu [4] reported a female MS patient with UDRV and attributed the occurrence of this phenomenon to the demyelinating plaques in the brainstem, which were observed on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of a "room tilt illusion" related to the SCA territory. [3][4][5] The SCA supplies the upper surface of the cerebellar hemisphere, superior vermis, dentate nucleus, upper portions of the middle cerebellar peduncle, superior cerebellar peduncle and lateral pontine tegmentum. Efferent fibers of the inferior cerebellar peduncle are mainly cerebellovestibular pathways.…”
Section: Room Tilt Illusion In Superior Cerebellar Artery Stroke: Arementioning
confidence: 99%